1. Suppose we have a transformation T: R^2 -> R^2 defined by T(x, y) = (2x + y, x - y). To find the matrix of this transformation with respect to the standard basis vectors e1 = (1, 0) and e2 = (0, 1), we can apply T to each basis vector and express the result as a linear combination of the basis vectors:
T(e1) = T(1, 0) = (2*1 + 0, 1 - 0) = (2, 1) = 2e1 + e2
T(e2) = T(0, 1) = (2*0 + 1, 0 - 1) = (1, -1) = e1 - e2
Therefore, the matrix of the transformation T with respect to the standard basis vectors is:
[2 1]
[1 -1]
2. Consider a transformation T: R^3 -> R^3 defined by T(x, y, z) = (x + y, y - z, x + z). To find the matrix of this transformation with respect to the standard basis vectors e1 = (1, 0, 0), e2 = (0, 1, 0), and e3 = (0, 0, 1), we can apply T to each basis vector and express the result as a linear combination of the basis vectors:
T(e1) = T(1, 0, 0) = (1 + 0, 0 - 0, 1 + 0) = (1, 0, 1) = e1 + e3
T(e2) = T(0, 1, 0) = (0 + 1, 1 - 0, 0 + 0) = (1, 1, 0) = e1 + e2
T(e3) = T(0, 0, 1) = (0 + 0, 0 - 1, 0 + 1) = (0, -1, 1) = -e2 + e3
Therefore, the matrix of the transformation T with respect to the standard basis vectors is:
[1 1 0]
[0 1 -1]
[1 0 1]